الاتجاهات المعاصرة في السنة في كتاب "السنة ودورها في الفقه الجديد" لجمال البنا : دراسة نقدية - مليحة، بومليك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study, in particular, examines the book by Jamal Al Banna, “Sunna and Its Role in the New Jurisprudence.” To some Muslims, Al Banna apparently has attacked the Sunnah and its long held traditions. However, this research hopes to clarify and argue that the Al Banna was not attacking the Sunna and its traditions. Rather, he attempted, in his book to dispel the rigid and inflexible interpretations by students and scholars which did not conform to the ideas of classical scholars of the living dynamism of the Hadith and the Sunna that transcend cultural and political boundary. The researcher hopes this study will help encourage more matured debates and discussions on Al Banna 's book.